An Examination of the Factors Associated With Implementation of Evidence‐Based Management Practices for Improving Nurse Work Environments. Issue 2 (18th March 2021) - Djukic, Maja; Jun, Jin; Fletcher, Jason
Abstract: Background: Evidence‐based management practices (EBMPs) that improve nurses' work environments have been linked to improvements in patient outcomes such as patient satisfaction and mortality. Yet, the extent to which nurse managers implement these EBMP or the factors associated with their implementation is not known. Aims: Guided by the Promoting Action on Research Implementation in Health Services (PARIHS) Framework, we examined individual, evidence, and organizational characteristics associated with nurse managers' implementation of the five EBMPs. Methods: A cross‐sectional, correlational, survey design was used. Nurse managers from 10 public hospitals in New York City were recruited. Evidence and contextual variables were measured with the Organizational Readiness for Change Assessment instrument. EBMPs were measured with a modified version of the Practice Environment Scale of the Nursing Work Index. All multi‐item scales were validated with confirmatory factors analysis in the studied sample. Additionally, the scales had Cronbach's alpha reliability greater than .8. A multivariate linear regression analysis with robust standard error correction was used to analyze the data and to adjust for clustering of managers in hospitals. Results: A total of 331 nurse managers responded for a 47.4% response rate. Bachelor's degree, number of staff supervised, managers' personal experience with evidence for EBMPs, staff culture, and organizational resources were significant predictors of nurse managers' implementation of EBMPs for NWE improvement ( p  < .05). Linking Evidence to Action: Staff culture was positively associated with implementation of all five EBMPs for improving nurses' work environments. Managers should prioritize nursing unit culture that encourages staff to innovate and change in order to improve care.